Relative justice [large type] - Whitlow, Robert, 1954- (Thorndike Press large print Christian fiction series., 2022)
"For the attorneys at Cobb and Cobb, the pursuit of justice is about more than legal expertise; it's a family matter. David Cobb is not a typical lawyer--he's more interested in dispensing God's wisdom than pertinent legal advice. High-stakes litigation is way outside his comfort zone. For many years Zeke Caldwell has been concocting home remedies made from natural ingredients found in the coastal marshes near Wilmington, North Carolina. One of his remedies proved so effective that he patented it with the help of David's father. Now he suspects a big drug company has stolen his formula. What he doesn't know is that the theft has deeper, more evil roots. When Zeke asks David to help fight the drug company, David knows the suit is beyond his expertise and experience. But his sister-in-law, Katelyn Cobb, is a rising star attorney in a prestigious Washington, DC, law firm. The courtroom is her second home. Could she help? Would she even consider it? Life's circumstances compel the lawyers to face, not only patent piracy, but personal obstacles and struggles that threaten to rip apart the fabric of the family. The fight for Zeke requires all the relatives to unite for justice. Praise for Relative Justice: "Robert Whitlow's legal expertise shines in Relative Justice, a story of patent infringement and illegal gains, but it's his characters who will steal the readers' hearts. Katelyn Martin-Cobbs, her husband Robbie, and his family face trials that allow them to heal old wounds and forge new bonds. Whitlow's fans are sure to enjoy going along"--